Pulmonary pathophysiology : - West, John B. (Williams & Wilkins, 1987)
A companion monograph to West's Respiratory Physiology, which examines normal respiratory function, Pulmonary Pathophysiology focuses on the function of the diseased lung. The text offers a clear, concise overview of the most essential information regarding disease states of the lung, emphasizing structure and function. A question and answer section is included. This 3rd edition offers more coverage of lung cancer and infectious diseases affecting the lungs, and has more tables to aid in rapid review